Multikulturalisme dalam Pendidikan Islam: Membangun Kesadaran dan Toleransi dalam Keanekaragaman Budaya - Barella, Yusawinur; Fergina, Ana; Achruh, Andi; Hifza, Hifza (Indo-MathEdu Intellectuals Journal, 2023)
Stereotypes, prejudices, and discrimination frequently emerge in Islamic educational environments, posing obstacles to personal growth, social integration, and the development of students' tolerance towards individuals and groups from diverse cultural backgrounds. The objective of this study is to comprehend and analyze how Islamic education can cultivate awareness and tolerance amidst cultural diversity. Qualitative research methodology, employing a literature review approach, was utilized in this study. The findings indicate that inclusive Islamic education should acknowledge and embrace cultural diversity as a positive aspect of learning. An approach that fosters awareness and tolerance towards cultural diversity is necessary. Furthermore, efforts are required to prevent and address stereotypes, prejudices, and discrimination within the educational setting. This research makes a significant contribution to the advancement of more inclusive and equitable Islamic education programs. The study's outcomes offer relevant recommendations for decision-makers, educators, students, and society in general, emphasizing the importance of nurturing awareness and tolerance towards cultural diversity tophold social harmony and inclusivity